Microbial diversity and its importance in microbial genetic resources preservation and its role in natural - Langkah Sembiring (The East Java Biological Society, 2015)
Biodiversity has been very common to almost every one. However, a comprehensive understanding on the concept of biodiversity might be less common to many discussing parties. Likewise, microbial diversity is even less common to most of academician, ex-cept of course to microbiologists. In fact, a correct and clear concept of biodiversity is prerequisite for serious and appropriate discussion of the matter. In this paper, the concept and understanding of microbial diversity is fundamentally described as well as their genetic potential by reviewing the development and application of species concept based on molecular biological approach. It is an undeniable fact that molecular biology has provided a powerful tool for microbiologists as well as evolutionists to unravel the biodiversity of microbial world which play a paramount important to conserve the basic function of any natural environments in the biosphere since microbes live and flourish in all ecosystems, including extreme habitats. The ubiquity of microbes clearly underpins by their diversity, including physiological and metabolic diversity, ability to live in anaerobic environments, and their small size. Molecular biology development and application in microbiology have transformed the three areas in microbiology, namely microbial ecology, microbial diversity, and microbial evolution from weakness into the strength, in unraveling and understanding microbial diversity and its genetic potential as well as its role in nature, especially their role to keep work the biogeochemical cycle in the Earth. Only by having an adequate understanding of microbial critical role in preserving nature that the environmental conservation issue could be carried out, understood and realized meaningfully.